PENGARUH PELATIHAN TERHADAP PENGETAHUAN KADER TENTANG ALAT KONTRASEPSI - Nurwita, Ati (JURNAL KESEHATAN KARTIKA, 2020)
Since 1970, the family planning program has been a national program.This program was aimed to reduce birth rates and improve the quality and well-being families.The problem showed in the family planing program is unmet need, that show description of disparities in family planning services.Indonesia’s target to reduce unmet need in 2020 is 7,7 %, while the achievement based on the IDHS (2017) is 10,5 % (Kemenkes, 2018) . One of the achievement targets is the ease of access to family planning service(Kemenkes, 2014). The stategy promoted is to increase the participation of community group to increase the ability of community knowledge and understanding offamily planning, one of which is to involve health cadres in the community (Kemenkes, 2020). To improve the cadres capabilities regarding the family planning program, training was conducted. This study was aimed to measure the effect of training on cadres’ knowledge of contraseption. This study is analitic with One Group Pre-tes Post tes One Design (Sugiono, 2011). Numbers of respondens were 15 respondens. Instrument of this study is questionnaire. Bivariate analysis with paired sample t test (Dahlan, 2013). The analysis showed that training and cadres’ knowledge of various contraseptives is not significantly correlated with mean difference 7,22 and significancy value 0,155 (p <0.005). Based on the result of this study showed increase mean score of knowledge from 63, 9 to 71,12, this result could be influenced by other factors. Including age (mean 45,5) and the lengt of time become a cadre (mean 5,3) (Azwar, 2012) with almost a part education of cadre is high school (46,7 %). The training management process also plays a role in the success of the training (Siregar, 2018). Can be developed with a integrated module training on family planing(Sundari et al., 2019)